ANALISIS PERKEMBANGAN ANAK USIA DINI DI TK ABA SUNGAI LIMAU - Nuraisyah; Afrinaldi; Fadhilla Yusri; Linda Yarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by issues related to the analysis of early childhood development at TK ABA Sungai Limau. The problem arises from the importance of understanding children’s developmental processes, including physical, psychosocial, and socio-emotional aspects, which have not been thoroughly analyzed in this setting. Therefore, this study aims to identify and describe early childhood development at TK ABA Sungai Limau. This research employs a field research design with a qualitative approach. It was conducted in Padang Pariaman Regency, with teachers and parents of TK ABA Sungai Limau students as the main informants. Data were collected through observation and interviews. The data were analyzed using a descriptive method, which systematically describes the actual conditions found in the field. The results show that early childhood development is a continuous, progressive process that cannot be repeated. It involves relatively permanent changes influenced by physical maturity, cultural demands, and individual values and aspirations. Children who successfully accomplish developmental tasks tend to achieve well-being and success in subsequent stages, while failure may hinder further development. Overall, children’s development at TK ABA Sungai Limau includes psychosocial and socio-emotional aspects that develop in accordance with their age stages.